Microbial and enzymatic activities in the soil after application of retorted oil shale - Doumer, Marta Eliane; Giacomini, Sandro José; Silveira, Carlos Augusto Posser; Weiler, Douglas Adams; Bastos, Leonardo Mendes; de Freitas, Luana Liberalesso (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this study was to assess the effect of increasing doses of retorted oil shale (ROS) application on the biological property indicators of soil quality. Experiments were carried out, under field and laboratory conditions, on a Hapludalf soil. In the laboratory, the treatments consisted of the application of seven different ROS rates (0, 300, 450, 600, 750, 1,500 and 3,000 kg ha-1) to the soil. In the field, the treatments were composed by four different ROS rates (0, 750, 1,500 and 3,000 kg ha-1) combined with the recommended mineral fertilizer rate, evaluated in two croppings of common bean (Phaseolus vulgaris L.), under no-till system. CO2 evolution, microbial biomass carbon (MBC), soil enzyme activity and the ecotoxicity test were evaluated. Application of increasing ROS rates improved the soil microbial activity by decreasing CO2 emission and causing no variations in MBC nor negative impacts on the soil enzymatic activity. The results obtained with the enzymes under field conditions, after two ROS applications, allied to MBC results, and to the metabolic quocient (qCO2) and to the ecotoxicity test, under laboratory conditions, show that the use of ROS cause no soil biological degradation.